The clinical characteristics of pediatric coronavirus disease 2019 in 2020 in Japan. Issue 1 (10th November 2021) - Katsuta, Tomohiro; Shimizu, Naoki; Okada, Kenji; Tanaka‐Taya, Keiko; Nakano, Takashi; Kamiya, Hajime; Amo, Kiyoko; Ishiwada, Naruhiko; Iwata, Satoshi; Oshiro, Makoto; Okabe, Nobuhiko; Kira, Ryutaro; et al.
Abstract: Background: The COVID‐19 pandemic has affected the lives of people of all ages. Most reports on pediatric cases suggest that children experience fewer and milder symptoms than do adults. This is the first nationwide study in Japan focusing on pediatric cases reported by pediatricians, including cases with no or mild symptoms. Methods: We analyzed the epidemiological and clinical characteristics and transmission patterns of 840 pediatric (<16 years old) COVID‐19 cases reported between February and December 2020 in Japan, using a dedicated database which was maintained voluntarily by members of the Japan Pediatric Society. Results: Almost half of the patients (47.7%) were asymptomatic, while most of the others presented mild symptoms. At the time of admission or first outpatient clinic visit, 84.0% of the cases were afebrile (<37.5°C). In total, 609 cases (72.5%) were exposed to COVID‐19‐positive household members. We analyzed the influence of nationwide school closures that were introduced in March 2020 on COVID‐19 transmission routes among children in Japan. Transmission within households occurred most frequently, with no significant difference between the periods before and after declaring nationwide school closures (70.9% and 74.5%, respectively). Conclusions: COVID‐19 symptoms in children are less severe than those in adults. School closure appeared to have a limited effect on transmission. Controlling household transmission from adult family members is the most important measure for prevention of COVID‐19 among children.